A simple and efficient system for evaluating plant genome editing efficiency and its application in optimizing the ISAam1 TnpB nuclease - Cao, Xingyu; Bai, Shasha; Li, Jun; Sun, Yongwei (Frontiers in Plant Science, 2025)
Genome editing technology has revolutionized plant genetic breeding. However, Significant variability in editing activity has been observed across different genome editing systems and target sites, highlighting the importance of developing efficient evaluation systems for assessing genome editing efficiency in plants. In this study, we developed a simple, rapid, and efficient system based on hairy root transformation to evaluate somatic genome editing efficiency in plants. This system is easy to implement, does not require sterile conditions, and enables visual identification of transgenic hairy roots within two weeks. We first validated the system using the CRISPR/Cas9 genome editing platform, confirming its effectiveness. Subsequently, we applied this system to assess the somatic editing activity of the recently identified ISAam1 TnpB nuclease, which show considerable promise for plant genome editing applications. Furthermore, through protein engineering, we identified two variants, ISAam1(N3Y) and ISAam1(T296R), which exhibited a 5.1-fold and 4.4-fold enhancement in somatic editing efficiency, respectively. These findings demonstrate that the developed method provides an effective tool for optimizing genome editing system and screening potential target sites in plant genomes.